The Post-training Needs of School Counsellors and its Influence on Practice in Selected Public Secondary Schools of the Mezam and Mfoundi Divisions of the North West and Center Regions of Cameroon - Claudine, Tantoh Mengwi (Journal of Innovation in Education and Social Research, 2024)
There is high recognition that knowledge, skills and attitudes are critical in effective counselling practice and this is the rationale for counsellor’s training and development. This study examined the post-training needs of school counsellors and its influence on practice. The concurrent nested mixed-method research design was used. Quantitative data was collected through descriptive survey with the aid of a questionnaire while qualitative data was collected using an interview guide. A sample of 249 randomly selected school counsellors were recruited from secondary schools in Mezam and Mfoundi Divisions of Cameroon. Quantitative data was analysed using descriptive and inferential statistical tools; frequency counts, graphs, percentages and the Pearson test and regression analysis was used to test hypotheses. Thematic analysis with the aid of themes and quotations was used for qualitative data. Findings showed a significant, positive and strong influence on practice (R-value=0.611**, p-value=0.000<0.05). Implications are that the quality of training being offered to counsellors be intensified and improved. It was recommended that school counsellors be trained to be multiskilled, the training be intensified with emphasis on practicum; appropriate and adequate programs be organized and appropriately delivered by those who master the content at divisional and regional levels for counsellors to upgrade their skills.